Disrupting from the Inside: UK Archipreneurs. (2nd March 2020) - Castle, Helen
Abstract: No longer restricted to designing buildings, architectural practices are seizing the opportunity to diversify. They are redefining the architect's role by embracing a wide variety of relationships up and down the design and construction procurement chain, utilising new technologies for digital fabrication, development economics and building performance analysis, as well as advising clients on their business models. RIBA Publishing Director Helen Castle, former Editor of 2, describes how this shift is panning out in the UK.